Coherence in the Qurʾān: principles and applications - Khan, Israr Ahmad (IIUM Press, 2002)
The differences and at times seemingly contradictory interpretation of Qurʾanic āyāt (verses) by scholars belies the notion that the Qurʾanic message is universal and relevant to all situations and settings. One reason for this problem is the erroneous belief that the Qurʾanic āyāt do not form an integral whole. It needs be emphasized that the Qurʾanic statements constitute an integral whole. To appreciate this integral aspect of the Qurʾanic statements, it is necessary to identify the linkages among āyāt of a surah (chapter) by following certain principles.